Caring alone? Social capital and the mental health of caregivers - Lars Thiel (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This study analyzes the role of social capital in buffering the negative relationship between informal-care provision and mental health. Using data from the German Socio-Economic Panel (SOEP) and fixed-effect regression models, we show that those individuals who socialize more frequently enjoy better mental health. We also find that stronger social ties moderate the negative association between caregiving and mental well-being. The protective role of social capital appears to be particularly strong for caregivers with high time commitments or those who regularly perform voluntary work. The moderating role of social activities can neither be explained by the caregiver's observed characteristics correlated with social capital, nor by features of the caregiving process. However, the results might be driven by insuficient overlap in covariates between carers and non-carers, and the simultaneity between caring decisions and social activities. We relate our results to recent policy initiatives that aim to improve the carer's well-being. Utilization of caregiver-support services is still rather low. Our findings suggest that caregivers may prefer informal support provided by family, friends, or neighbors to public caregiver benefits. To corroborate this hypothesis, further research regarding the (causal) buffering effects of social capital in the context of informal care is needed.
Keywords: I10; J14; Z13; 330; informal care; social capital; mental health